Comparison of hemogram parameters according to the severity of Vitamin B12 deficiency in children aged three months-16 years - Büke, Övgü; Erol, Meltem; Bostan Gayret, Özlem; Yiğit, Özgül; Mete, Fatih (Progress in Nutrition, 2020)
IntroductionVitamin B12 is essential for neurological development in childhood. Anemia, leukopenia, and thrombocytopenia can be listed among hematologic findings in vitamin B12 deficiency, however, these changes occur in the advanced stages. The objective of this study was to investigate the relationship between the severity of vitamin B12 deficiency and hemogram parameters and to evaluate the value of hemogram parameters in early detection of vitamin B12 deficiency.Materials and MethodsThe patients were divided into two groups. A vitamin B12 level ≤200 pg/mL was considered severe deficiency (Group 1) and a vitamin B12 level >200 pg/mL was considered as a moderate deficiency (Group 2). Vitamin B12 level, hemoglobin, hematocrit, red cell distribution width, platelet count, mean erythrocyte volume, mean platelet volume, lymphocyte and neutrophil counts were compared between the two groups.ResultsThe mean red blood cell count (RBC) in Group 1 was significantly lower than in Group 2 (p=0.047) and  the mean red cell distribution width (RDW) in Group 1 was significantly higher than in Group 2 (p=0.003). The mean hemoglobin and hematocrit levels in Group 1 was found to be significantly lower than in Group 2 (p=0.026 and  p=0.025).As a result of the logistic regression analysis performed with these parameters, it was observed that the only factor affecting vitamin B12 deficiency in children in our region was elevated RDW (p=0.01). ConclusionIn this study, it was observed that only elevated RDW can be used as an early indicator of vitamin B12 deficiency in children.